Loyal Macabebes how the Americans used the Macabebe scouts in the annexation of the Philippines - Flake, Dennis Edward (Juan D. Nepomuceno Center for Kapampangan Studies, Holy Angel University, 2009)
"This book traces the events that convinced the United States government to adopt the practice of pitting one native tribe against another to win their war on foreign soil--a policy that has since defined US involvement in similar wars."--Back cover.